Description of Family Knowledge about Clean and Healthy Living Behavior in Tarowang Village, South Galesong District, Takalar Regency - Nurhijrani Nurhijrani; Asriani Bahar (Sean Institute, 2023)
Based on data from Tarowang Village in 2020, the number of heads of families in Tarowang Village is 627. It is recorded that there is still a lack of public awareness of the importance of clean and healthy living behaviors. The aim of this research is to obtain an overview of family knowledge about clean and healthy living behavior in Tarowang Village, South Galesong District, Takalar Regency. The research method used is a descriptive research method where the research will describe the family's knowledge about clean and healthy living behavior in Tarowang Village, South Galesong District, Takalar Regency. The results of research conducted on 85 respondents showed that the number of respondents whose knowledge about clean living behavior was good was 56 (65.88%), while 29 (34.11%) had poor knowledge. The conclusion of this research is that family knowledge about clean and healthy living behavior in Tarowang Village, South Galesong District, Takalar Regency is quite good; out of 85 respondents, 56 (65.88%) have knowledge. The level of knowledge is good, and 29 respondents still have less knowledge, namely 34.11%. The inhibiting factors in the lack of knowledge about clean and healthy living behavior are mostly caused by a lack of public awareness and an inadequate educational background.